Similarity of supply and demand shocks between the euro area and the accession countries - Jarko Fidrmuc; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
We assess the correlation of supply and demand shocks between the euro area, the EU accession countries and also the present EU countries.Shocks are recovered from estimated structural vector autoregressive models.We find that some advanced accession countries have quite high correlation with the euro area.However, even for many high income accession countries the degree of correlation remains low.Also, in the 90s many EU countries seemed to have much higher correlation with the core euro area countries than in previous decades.Continuing integration within the EU seems to have aligned business cycles of the countries as well.
URN:NBN:fi:bof-201408072186
Keywords: E32; F42; 330; optimal currency area; monetary union; EU enlargement